The Maze of APP Processing in Alzheimer’s Disease: Where Did We Go Wrong in Reasoning? - Chen, Ming (Frontiers in Cellular Neuroscience, 2015)
Late onset sporadic Alzheimer’s disease (sAD) has remained a conundrum after vigorous studies today, and the main reason is the stagnation in understanding the mechanism of origins of plaques and tangles. While they are widely thought to be the “culprits” of the disease or products of the “aberrant” pathways, we believe that plaques and tangles result from natural aging. From this new perspective we have proposed that age-related inefficiency of α-secretase is the underpinning for Aβ overproduction. This view contrasts sharply with the current doctrine that Aβ overproduction is the product of the “overactivated” β- and γ-secretases. Following this doctrine it has been claimed that the two secretases are “positively identified” and that their inhibitors have “successfully reduced Aβ levels”. But, why have these studies not led to the understanding of the disease? And if so where did they go off course in reasoning? These questions touch the basics of biological science and must be answered. In this paper I dissected several prevailing assumptions and influential reports with an attempt to trace the origins of the conundrum. This work led me to a new model for Aβ overproduction and also to a serious question: given the knowledge that boosting α-secretase reduces Aβ, a straightforward highway for intervention, then why is there such an obsession on “inhibiting β- and γ-secretases”, a much more costly and twisting road even if possible? This issue requires the attention of policymakers and all researchers. I therefore call for a game change in sAD study.